The Dynamics of Celebrity Involvement in The Reform Period Legislative Elections (2004-2024) - Amir; Reiza D Dienaputra; Yuddy Chrisnandi; N. Kartika (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
The conduct of legislative elections in Indonesia during the Reform Era (2004–2024) demonstrates a tendency among political parties to leverage celebrity popularity as a strategy to boost their vote acquisition. The shift to an open-list proportional electoral system, based on the highest number of individual votes, has driven parties to recruit celebrities as vote-getters to increase their electoral gains. This study aims to analyze party strategies in positioning celebrities as legislative candidates and to identify electoral districts (dapil) that are most favorable to their electability. Using historical research methods and analyzing data from the past five legislative elections, the study finds that West Java has emerged as the strongest electoral base for celebrity candidates. One key strategy employed is the Son of the Soil approach, which utilizes regional identity to foster emotional connections with voters. The findings highlight that local identity plays a significant role in celebrity electoral strategies, making cultural and emotional affiliations crucial factors in their electoral success.